Compatibility in thermoelectric material synthesis and thermal transport - Ariyo Nurachman Satiya Permata; Christian Idogho; Catur Harsito; Ilogho Thomas; Abel Ejila John (Unconventional Resources)
Thermoelectric materials show promise in energy conversion uses such as high-temperature power creation and waste heat recapture. This study explores synthesised Holmium-Antimony-Tellurium (Ho-Sb-Te) materials, as well as how they perform together compatibly, and expertly deposits them using pulsed electrodeposition onto Bi2SbTe3, Zn2Sb3, and SiGe, substrates to optimally control stoichiometry. The Seebeck coefficient, electrical resistivity, thermal conductivity, as well as the figure of merit (ZT) were thermoelectric properties. These properties were carefully measured experimentally within the 300–1250 K range. The simulations within Ansys Workbench did assess several compatibility factors. Efficiency greatly improves as a result of increasing the operating temperature, and the leg-pair (2 pairs, 3 pairs and 4 pairs), results show, with peak values of 23.68 %, 36.24 % and 46 %, respectively. SiGe had a compatibility factor in the range of 1100–1250 K, which was the highest, and this observation confirmed that it is well-suited for high-temperature TEGs. N-type materials, as a class, exhibited superior levels of thermal and charge transport, thereby rendering them ideal for efficient heat management. This work guides the selection of materials for the improvement of thermoelectric power generation, optimizes leg geometry, and synthesizes techniques. In the future, we will explore composite materials. We will also evaluate thermal cycling reliability for real-world deployment of it.